Answer:
Y'=3xy-3x-12
Y'=F(-2,-1)=0
Step-by-step explanation:
The function of the equation at the point (-2,-1)
is where the equation make the function go to zero:
Y'=3xy-3x-12
Y'=F(-2,-1)=[3(-2)(-1)]-[3(-1)]-12
F(-2,-1)=[6]-[-6]-12
F(-2,-1)=6+6-12
F(-2,-1)=12-12
F(-2,-1)=0
Solving for y
3xy-3x-12=0
y=4/x+x
Making y=0
![\frac{4}{x}+x=0](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7Bx%7D%2Bx%3D0)
![x^{2} =-4](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%3D-4)
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
So the values make the function go to zero
Answer:
24
Step-by-step explanation:
the rate of change is represented by the 24, just like in the slope-intercept equation y = mx + b, where "m" represents the slope, or rate of change.
Answer:
6.67408 × 10^-11 m^3 kg^-1 s^-2
Step-by-step explanation:
F = G M 1 M 2 d 2 , where F is the gravitational force between two point masses, M1 and M2; d is the distance between M1 and M2; G is the universal gravitational constant, usually taken as 6.670 × 1011 m3/(kg)(s2) or 6.670 × 10−8 in centimeter–gram–second units. a = F M 1 = G M 2 r 2 .
Answer:
no
Step-by-step explanation:
A full turn is 360 degrees, so 25 desgrees